1987
DOI: 10.1002/jobm.3620270604
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture conditions on mycelial structure and polygalacturonase synthesis of Aspergillus niger

Abstract: Biosynthesis of polygalacturonase (PG) by A. niger strain R 1/214 correlates with the morphology of mycelium in submerged culture. The mean specific PG-synthesis (PG-U.g-1.h-1) increases with the degree of compactness of mycelium. PG-production can be optimized by a precise adjustment of the culture conditions after direct spore inoculation (diffuse mycelium) but the high synthesis as by compact mycelium is never obtained. Different reasons for the higher enzyme production by the pellet mycelium are discussed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 5 publications
(1 reference statement)
0
22
0
Order By: Relevance
“…4). However, it should not be overlooked that enhancement of PG production in pellet form can be partly a result of altered cellular metabolism and enzyme secretion due to limitations in oxygen and nutrient supply and in removal of metabolic products [42].…”
Section: Effect Of Spore Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…4). However, it should not be overlooked that enhancement of PG production in pellet form can be partly a result of altered cellular metabolism and enzyme secretion due to limitations in oxygen and nutrient supply and in removal of metabolic products [42].…”
Section: Effect Of Spore Concentrationmentioning
confidence: 99%
“…In another study, where agro-based products were utilized for exo-PG production by A. sojae M5/6, the inoculum size of 4 9 10 5 spores/mL resulted in mycelial clumps and viscous culture broths in the presence of all substrates [8]. Hermersdörfer et al [42] observed increased PG synthesis by A. niger in a synthetic medium when it grew as a compact mycelia, which was defined as a large ball with a diameter of 40 mm. The PG activity was considerably lower when the growth was in the form of either diffuse mycelia or pellets of 2-10 mm in diameter [42].…”
Section: Effect Of Spore Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sucrose 24.0, (NH4)2SO4 5.0, MgSO4.7H2O 0. were added to the fermentation medium, based on the values proposed in the literature for citric acid or pectinolytic enzymes production (1,12,17). Table 1 shows the levels adopted for this study.…”
Section: Basal Medium Composition (G/l)mentioning
confidence: 99%
“…The relationship between the fungi morphology and the enzyme production in submerged fermentation has also not been widely reported. In shake flask fermentation, the growth of diffuse and compact mycelia by A. niger strains for polygalacturonase synthesis was studied by Hermersdörfer et al (12). They found a direct correlation between the compactness of the pellet and the polygalacturonase synthesis, but despite having used trace metals as micronutrients, the authors excluded reference to them in their final conclusions.…”
Section: Introductionmentioning
confidence: 99%